Male suicide among construction workers in Australia: a qualitative analysis of the major stressors precipitating death - Allison Milner; Humaira Maheen; Dianne Currier; Anthony D LaMontagne (BMC, 2017)
Abstract Background Suicide rates among those employed in male-dominated professions such as construction are elevated compared to other occupational groups. Thus far, past research has been mainly quantitative and has been unable to identify the complex range of risk and protective factors that surround these suicides. Methods We used a national coronial database to qualitatively study work and non-work related influences on male suicide occurring in construction workers in Australia. We randomly selected 34 cases according to specific sampling framework. Thematic analysis was used to develop a coding structure on the basis of pre-existing theories in job stress research. Results The following themes were established on the basis of mutual consensus: mental health issues prior to death, transient working experiences (i.e., the inability to obtain steady employment), workplace injury and chronic illness, work colleagues as a source of social support, financial and legal problems, relationship breakdown and child custody issues, and substance abuse. Conclusion Work and non-work factors were often interrelated pressures prior to death. Suicide prevention for construction workers needs to take a systematic approach, addressing work-level factors as well as helping those at-risk of suicide